1992
DOI: 10.1159/000126090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocaine and Pimozide on Plasma and Brain Alpha-Melanocyte-Stimulating Hormone Levels in Rats

Abstract: The effects of cocaine on rat plasma and brain α-melanocyte-stimulating hormone (α-MSH) levels have been studied by means of a specific radioimmunoassay. The selected brain areas were the hypothalamus, septum-nucleus ac-cumbens and hippocampus. Cocaine given subcutaneously decreased the α-MSH levels in the peripheral blood. Pimozide, a dopaminergic antagonist, had an opposite effect: it increased the α-MSH levels in the peripheral blood. Combined treatment with cocaine + pimozide resulted in a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Meanwhile, decreasing MC4R enhances glutamatergic signaling in the striatum 17 . Given that dopamine agonists increase POMC, the precursor for α-MSH 42 , and cocaine increases striatal α-MSH content 43 , rewarding events may result in α-MSH-MC4R binding. This binding would cause GluA2-AMPAR internalization, decreasing the synaptic sensitivity of DMS MSNs to cortico-striatal glutamatergic afferents, which otherwise trigger response plasticity and suppression in many contexts 44 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, decreasing MC4R enhances glutamatergic signaling in the striatum 17 . Given that dopamine agonists increase POMC, the precursor for α-MSH 42 , and cocaine increases striatal α-MSH content 43 , rewarding events may result in α-MSH-MC4R binding. This binding would cause GluA2-AMPAR internalization, decreasing the synaptic sensitivity of DMS MSNs to cortico-striatal glutamatergic afferents, which otherwise trigger response plasticity and suppression in many contexts 44 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be that loss of melanocortins in Pomc -/- mice are exerting an effect upon the central rewarding system to favour fat consumption. Given the localization of POMC and MC4-R in brain reward regions (33-35) and functional interactions with psychostimulants (36;37), there is certainly evidence indicating melanocortins may have a role beyond that of helping to integrate a response to nutrient sensing. Genetically modified mice with selective loss of POMC fragments in specific brain regions may be useful to bring about a fuller clarification of such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in vitro studies demonstrate that α‐MSH stimulates cAMP production via interactions with dopamine D1 receptors (Lezcano et al ., 1995; Cremer et al ., 2000). Activation of dopamine neurotransmission, by administration of either a direct‐acting dopamine agonist or an indirect agonist like cocaine, is also reported to upregulate POMC expression in the arcuate nucleus and melanocortin neuropeptide levels in nucleus accumbens (Sarnyai et al ., 1992; Tong & Pelletier, 1992). Finally, one recent study demonstrated that infusion of a melanocortin agonist into the lateral ventricle enhances the effects of amphetamine on lateral hypothalamic self‐stimulation (Cabeza de Vaca et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%